INTERAKSI DALAM SOLUSI SOLITON TEORI MEDAN AFFINE TODA - Hidayati
Abstract : The affine Toda field theory is an example of a two-dimensions integrabel field theory . In the imaginary regime of the coupling parameter, the affine Toda field theory admits multisolitons solution, which, for example, can be determined by Hirota method. From the 2-solitons solution we can build a soliton boundstate solutions. In this affine Toda field theory the effect of collision of 2-solitons is a time delay of their final trajectories relative to their initial trajectories. Classically, the time delay can be calculate from interactions of classical multisolitons solution. On the other hand, semiclassical description of collision of quantized soliton wave can be derived from their classical limit of the scattering-matrices. In this thesis we study the collision between soliton-soliton, boundstate-soliton and boundstate-boundstate. For each interaction processes above it was found that both of time delay have same value.